Hyperthermal atomic oxygen durable transparent silicon-reinforced polyimide. (September 2019) - Qian, Min; Xuan, Xiao Yang
A clear poly(amic acid) was reinforced by a trisilanolphenyl polyhedral oligomeric silsesquioxane (POSS) by direct dissolution, and transparent silicon-reinforced polyimide (Si-RPI) films with different POSS loadings were obtained after curing, showing high transmittance of >90% within 380–800 nm. The Si-RPI films were exposed to a ground hyperthermal atomic oxygen (AO) beam. The erosion depths and derived erosion yields of the materials decreased with POSS loadings. At a 20 wt% POSS loading, the Si-RPI showed an erosion yield of 0.13 × 10 −24 cm 3 atom −1 at a fluence of 2.79 × 10 20 O atoms cm −2 . Surface morphology and element composition characterization on Si-RPI indicated that SiOx -based passivating layers were formed on surfaces upon the hyperthermal AO attack. This study suggests a facile way of reinforcing Si into transparent polyimide for a promising candidate of spacecraft coating material operating in low Earth orbit.